Thermal shock behaviour of mullite-cordierite refractory materials - Boccaccini, Aldo R.; et al. (Advances in Applied Ceramics, 2007)
The characterisation of thermal shock damage in cordierite-mullite refractory plates used as substrates in fast firing of porcelain whiteware has been investigated. Two different refractory compositions (termed REFO and CONC), characterised by different silica to alumina ratios, were studied. Thermal shock damage was induced in as received samples by water quenching tests from 1250°C. Thermal and mechanical properties were measured at room temperature by means of standard techniques and then the thermal shock resistance parameter R was calculated. The fracture toughness of selected samples was measured before and after thermal shock by the chevron notched specimen technique. The reliability of this technique for evaluation of small differences in fracture toughness after a given number of thermal shock cycles was investigated. The suitability of Klc measurements by the chevron notched specimen technique to characterise the development of thermal shock damage in refractory materials was proved in this investigation. © 2007 Institute of Materials, Minerals and Mining.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.therma_5
Keywords: Fracture toughness; Refractory materials; Thermal shock